Elevating Gen-Z’s Scientific Literacy through Interactive Learning Multimedia - Natsir, Siti Zahra Mulianti; Rubini, Bibin; Ardianto, Didin; Karimatunnisa, Karimatunnisa (Universtas Negeri Makassar, 2024)
The study explores the effectiveness of interactive learning multimedia in boosting Gen-Z’s scientific literacy. There were 46 Gen-Z were involved from 2 (two) junior high school in Makassar. The research design was one group pretest-posttest design and the data collection used a set of scientific literacy test (multiple choices) and a questionnaire on the attitude towards science. There were 3 (three) domains of scientific literacy were measured namely; competency, knowledge, and attitude towards science. The result proves that the interactive multimedia is effectively enhance Gen-Z’s scientific literacy with n-gain value of average is 0,62 or in moderate category. The interactive multimedia was implemented using problem- based learning method which also contributed to the improvement of gen-Z’s scientific literacy. Moreover, the interactive multimedia is equipped with learning material including simulations which organized according to the students’ need as well as the existence of virtual laboratory allowed Gen-Z’s to sharpening their understanding about the given material. Ultimately, the presence of digital interactive multimedia is unconsciously taking part to the government’s initiatives to enhance the digital literacy among the citizens in education sector. KeyThe study explores the effectiveness of interactive learning multimedia in boosting Gen-Z’s scientific literacy. There were 46 Gen-Z were involved from 2 (two) junior high school in Makassar. The research design was one group pretest-posttest design and the data collection used a set of scientific literacy test (multiple choices) and a questionnaire on the attitude towards science. There were 3 (three) domains of scientific literacy were measured namely; competency, knowledge, and attitude towards science. The result proves that the interactive multimedia is effectively enhance Gen-Z’s scientific literacy with n-gain value of average is 0,62 or in moderate category. The interactive multimedia was implemented using problem- based learning method which also contributed to the improvement of gen-Z’s scientific literacy. Moreover, the interactive multimedia is equipped with learning material including simulations which organized according to the students’ need as well as the existence of virtual laboratory allowed Gen-Z’s to sharpening their understanding about the given material. Ultimately, the presence of digital interactive multimedia is unconsciously taking part to the government’s initiatives to enhance the digital literacy among the citizens in education sector. Keywords: Gen-Z; Interactive Learning Multimedia, Substance Pressure, Scientific Literacy